Availability of four energy crops assessing by the enzymatic hydrolysis and structural features of lignin before and after hydrothermal treatment. (1st January 2018) - Li, Han-Yin; Wang, Bing; Wen, Jia-Long; Cao, Xue-Fei; Sun, Shao-Ni; Sun, Run-Cang
Highlights: The availability of four energy crops during hydrothermal treatment was assessed. Anatomical and chemical features synergistically affected the enzymatic hydrolysis. Hybrid Pennisetum was proved to be a promising feedstock for bioethanol production. The structural features of residual lignin were analyzed for further utilization. Abstract: The anatomical characteristics, chemical composition, enzymatic hydrolysis efficiency and lignin characteristics of four energy crops (switchgrass, Miscanthus × giganteus, Hybrid Pennisetum, and Triarrhena lutarioriparia ) before and after hydrothermal treatment (180 °C, 1 h) were investigated comprehensively to evaluate their potential for the bioenergy production. The hydrothermal treatment resulted in the deconstruction of the biomass cell walls and redistribution of the main components, accompanying with the removal of most hemicelluloses and partial lignin as well as favorable exposure of cellulose. These alterations significantly increased the efficiency of enzymatic hydrolysis, and the different recalcitrance of the four feedstocks was evenly erased by hydrothermal treatment. Among the four crops, Hybrid Pennisetum with high cellulose and low lignin contents had a better performance in the enzymatic hydrolysis process both before and after treatment. Meanwhile, the maximum concentration of low degree of polymerization xylo-oligosaccharides (2-6) and the lowest amount of degraded products were obtained from Hybrid Pennisetum during the treatment process. Moreover, the structural features of the residual lignin in the treated substrates were elaborately analyzed for deeply understanding the fundamental chemistry of lignin during the treatment. The present study is beneficial to the fully effective utilization of biomass components and extension of the energy sources.